Emotionalism Following Brain Damage - Peter Allman (Behavioural Neurology)
Emotionalism is an heightened tendency to cry, or more rarely, laugh. It is commonly associated with brain damage and is often distressing to both patients and carers. Emotionalism is easily confused with depression, and when severe it can interfere with treatment. The aetiology is poorly understood but its response to drugs with different modes of action suggests that there is more than one underlying mechanism. When the components of emotionalism are studied separately a wide range is observed and they combine in a more complex and varied way than commonly held stereotyped views suggest. Most patients with emotionalism are helped by simple education and reassurance. Some severe cases respond dramatically to tricyclic antidepressants, levodopa or fluoxetine.